HUBUNGAN ANTARA DIMENSI-DIMENSI SCHOOL WELL-BEING DENGAN MOTIVASI BERPRESTASI PADA SISWA KELAS X DI SMA UNGGULAN - Dhani Irmawan (Universitas Mercu Buana Jakarta, 2019)
The aim of this study is to find out the correlation between School Well-Being with Achievement Motivation at year X student in Senior High School Plus. The type of this study is ex post facto field study. Achievement Motivation consist of 65 item which measured with achievement motivation scale. School Well-Being, divided by four dimensions having, loving, being and health which measured with school well-being scale consist of 96 item. The result with partial correlation of this study shows that there is no significant correlation between having with achievement motivation (r= .0708, p> .01), also at loving with achiement motivation (r= .0161, p> .01) and health with achievement motivation (r= .5176, p< .01). At dimension of being, the result shows correlation between being and achievement motivation (r= .5176, p< .01). Therefore the dimensions of school well-being has correlation with achievement motivation only at being dimension. Base on the result of study, the discussion inform practical implication and suggestions for the next research and practical suggestion for school.